A present value concept for measuring welfare - Gerhard Rösl (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2024)
We create an alternative version of the present utility value formula to explicitly show that every store-of-value in the economy bears utility-interest (non-pecuniary income) for its holder regardless of possible interest earnings from financial markets. In addition, we generalize the well-known welfare measures of consumer and producer surplus as present value concepts and apply them not only for the production and usage of consumer goods and durables but also for money and other financial assets. This helps us, inter alia, to formalize the circumstances under which even a producer of legal tender might become insolvent. We also develop a new measure of seigniorage and demonstrate why the well-established concept of monetary seigniorage is flawed. Our framework also allows us to formulate the conditions for liability-issued money such as inside money and financial instruments such as debt certificates to become - somewhat paradoxically - net wealth of the society.
Keywords: D14; D60; E41; E50; 330; Welfare; money; seigniorage; net wealth